KEANEKARAGAMAN JENIS TUMBUHAN OBAT PADA KAWASAN HUTAN PRODUKSI DESA MALONAS KECAMATAN DAMPELAS KABUPATEN DONGGALA - Sajria, Sajria; Toknok, Bau; Rukmi, Rukmi (Jurnal Warta Rimba, 2019)
Medicinal plants are medicinal plants that can relieve pain, increase endurance, prevent and cure diseases. The use of natural materials as traditional medicine in Indonesia has been carried out by our ancestors since centuries ago until now still exists, especially in the village of Malonas, Dampelas District, Donggala Regency, Central Sulawesi Province. The purpose of this study was to determine the diversity of medicinal plants in the Production Forest area of Malonas Village, Dampelas District, Donggala Regency. This research was carried out in the production forest of Malonas Village, Dampelas Subdistrict, Donggala Regency, which was held for 2 months, from July to August 2018. This study used a single plot method which was purposively placed based on the location of medicinal plants. The minimum sample plot area used is determined by the area species curve. The results of the research conducted show that the number of seedlings and understorey medicinal plants that can grow in this area is greater, because the growth rate of the lower plants has a high diversity and species richness index influenced by the topography of the slope-sloping research site and at least cover from canopy at the level of growth of poles and trees. It can be seen from the results of calculation of tree level diversity index (H ') (0.69), pole level (0.61), stake level (0.63), seedling level and understorey (1.33). So the diversity of medicinal plants according to growth rates is generally classified as low.Keywords: Malonas Village Production Forest, Medicinal Diversity